A review of vortex water turbine design for sustainable energy generation (principles, optimization, and validation) - Zamzami; Akhyar Akhyar; Sarwo Edhy Sofyan; Suriadi; Khairil (Energy Conversion and Management: X)
This paper provides a thorough analysis of water vortex turbines, emphasizing their role in enhancing sustainable energy generation in situations of limited water flow. The research examines fundamental design elements such as the impact of water flow rate and basin size on turbine effectiveness. Additionally, it explores key factors in turbine blade design, such as shape, quantity, material composition, and the effects of turbine placement within the vortex on operational efficiency. The significance of optimization techniques in enhancing water vortex turbine technology is examined, with a specific focus on numerical optimization and computational fluid dynamics (CFD). These methodologies play a crucial role in enhancing turbine design to attain maximum performance outcomes. The analysis of design factors such as blade shape, blade angle, and flow configuration is essential in evaluating their influence on energy generation and effectiveness. The significance of experimental validation through prototype testing and performance analysis is also highlighted in this article. Prototype testing offers empirical data on shaft power, torque, and efficiency, while performance analysis involves comparing these findings with theoretical predictions to confirm the design’s effectiveness. The article explores advancements in intelligent water vortex turbine design, incorporating cutting-edge manufacturing methods like Computer-Aided Design (CAD) modeling, simulation, and 3D printing. This technology enables accurate design and production of intricate shapes, enhances turbine efficiency, and ensures efficient water sealing. In summary, this assessment underscores the significant promise of water vortex turbines in generating sustainable energy, particularly in regions with limited water flow. The incorporation of optimization methods and advanced manufacturing processes allows for the creation of highly effective and dependable water vortex turbines, establishing them as a feasible option in the realm of renewable energy. Suggestions for future research include enhancing turbine design and confirming its performance in practical settings.